Toward a Reality-Based Constitutional Theory - Andrew Coan (Washington University Law Review, 2011)
Despite the alleged triumph of legal realism and the empirical turn of closely related fields such as judicial behavior, a startling number of constitutional theorists continue to approach their work as a purely conceptual enterprise. This is particularly true of originalists, but it is true of many others as well. Indeed, much of normative constitutional theory as it is presently practiced resembles a recreational debating society more than a serious effort to improve the functioning of a massively complex modern society. If constitutional theory is to live up to its aspirations, a new reality-based approach is urgently needed. This brief Article makes the case for such an approach and offers practical suggestions for getting it off the ground.
Keywords: Constitutional law; Original intent (Law); United States